Social anxiety and alcohol consumption: The role of alcohol expectancies and reward sensitivity - Booth, C.; Hasking, Penelope (Pergamon, 2009)
Although the relationship between social anxiety and alcohol consumption has been the subject of extensive exploration, previous studies have failed to draw consistent conclusions about the nature of this relationship.Gray [Gray, J.A. (1970). The psychophysiological basis of introversion-extraversion. Behaviour Research and Therapy, 8, 249-266] suggested that individuals who are sensitive to reward are likely to place themselves in potentially rewarding environments (e.g. pubs and clubs). As such these individuals will have a greater chance to experience and vicariously observe the effects of alcohol in these environments, leading to the formation and modification of alcohol expectancies. Consequently, reinforcement sensitivity theory and alcohol expectancies are inherently related, yet have remained disparate areas of research. In this study, a total of 454 young adults responded to a questionnaire assessing social anxiety, alcohol consumption, reward sensitivity and alcohol expectancies. Regression analyses revealed a positive relationship between reward sensitivity, expectations of tension reduction and increased confidence, and alcohol consumption. Expectations of tension reduction were observed to moderate the relationship between social anxiety and alcohol consumption. In addition, three-way relationships between reward sensitivity, alcohol expectancies and social anxiety were observed to predict alcohol consumption. Overall, these results suggest that both reward sensitivity and alcohol expectancies play a role in the relationship between social anxiety and alcohol consumption, and that inclusion of these constructs in further research may aid in further clarifying the mechanisms underlying comorbid social anxiety and alcohol abuse.